Mapa da empatia em saúde na percepção do paciente (MES-PP): elaboração de um instrumento para avaliar a empatia clínica - Bernardes, Liliane Faria (2023)
Introduction: The relation between self-evaluated empathic capacity and the physicians' empathic behaviors correlates poorly, or not at all, with the patients' perspectives on the aspect of physician-patient interactions. Thus, any assessment of a physician’s empathy that aims a more concrete understanding of such interaction, must consider the patients' perspectives. Objective: To develop an instrument based on the Health Empathy Map (MES) to evaluate the empathic medical care of medical students from the perspective of the patient. Methodology: This is a descriptive study for the elaboration of an instrument capable of evaluating the empathy of medical students, from the perspective of the patient. The Study had five stages: 1. Revision of literature. 2. Development of an educational instrument to assess the practice of empathy in the health care setting, from the patient's perspective, based on the MES. 3. Semantic validation and analysis of the feasibility of the instrument using the Expert Panel technique. 4. Assessment of the feasibility of using the instrument in the learning environment. 5. Quantitative content analysis. Results: The adequacy of the instrument, to be used by patients in health education settings, took into account the conceptual pillars of empathy - perspective taking, emotional sharing and empathic concern - as well as the suggestions of specialists and the pre-tests carried out with patients. All suggestions were discussed by the researchers and accepted, after reaching a consensus that they indicated advances and improvements of the instrument, which could enable its use by patients in health learning environment. Conclusion: The final version of the Health Empathy Map in Patient’s Perception (MESPP) proved to be easy to understand and apply in the clinical learning environment and was considered, by the participants of the different phases of the study, as an educational tool with great instructional potential in regards to the development of empathy in the clinical learning scenario.